Preaching to the Laity in Fifteenth-Century Germany: Johannes Nider's ‘Harps’ - Dahmus, John (The journal of ecclesiastical history, 1983)
Bernd Moeller concludes in his often-quoted study of late medieval German piety that ‘one could dare to call the late fifteenth century in Germany one of the most churchly-minded and devout periods of the Middle Ages’. In his review of Moeller's work, W. D.J. Cargill Thompson points out that the ‘profound conservatism’ of this religiosity, which included devotion to the mass, veneration of saints and their relics, and the reading of vast amounts of religious literature, poses a problem for our understanding of the causes of the Reformation. How does one reconcile this traditional churchliness with the ‘remarkable suddenness’ of its collapse after 1520? One would have expected greater resistance to Lutheran ideas than actually occurred.